2018
DOI: 10.3389/fped.2018.00025
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Paracetamol in Closure of Ductus Arteriosus in Infants under 32 Weeks of Gestation

Abstract: BackgroundStandard medical treatment for patent ductus arteriosus (PDA) closure has been indomethacin/ibuprofen or surgical ligation. Up to date, new strategies have been reported with paracetamol. The aim of this study was to present our experience with intravenous paracetamol for closing PDA in preterm neonates presenting contraindication to ibuprofen or ibuprofen had failed and no candidates for surgical ligation because of huge instability.Materials and methodsWe conducted a retrospective case series study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Tofe et al (19) demonstrated that paracetamol was effective in PDA closure in premature neonates under 32 weeks of gestation. They showed that paracetamol was comparable to ibuprofen and indomethacin in treating PDA, with a closure rate of 77.7% observed in the paracetamol group vs. 81.1% in the ibuprofen group.…”
Section: Discussionmentioning
confidence: 99%
“…Tofe et al (19) demonstrated that paracetamol was effective in PDA closure in premature neonates under 32 weeks of gestation. They showed that paracetamol was comparable to ibuprofen and indomethacin in treating PDA, with a closure rate of 77.7% observed in the paracetamol group vs. 81.1% in the ibuprofen group.…”
Section: Discussionmentioning
confidence: 99%